Can all perfect cubes be written as the difference of two perfect squares?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us take x 2 − y 2 = k 3 , which is expressible as ( x + y ) ( x − y ) = k 3 . Now let us take the following system of equations:
x + y = k 2 ; x − y = k ⇒ x = 2 k 2 + k = 2 k ( k + 1 ) ; y = 2 k 2 − k = 2 k ( k − 1 ) .
Hence, x , y ∈ Z for all k ∈ Z and conclusively shows all perfect cubes can be expressed as the difference of two perfect squares.
QED
Problem Loading...
Note Loading...
Set Loading...
You might know that (1+2+3...n)^2=1^3+2^3+3^3...n^3.So (1+2+3...n)^2-(1+2+3...n-1)^2=n^3